Aplicação de um modelo numérico na otimização de fornos alimentícios usando o OpenFOAM® - Verdério Júnior, Sílvio Aparecido [UNESP] (2015)
Because of the better flexibility in warning and high production, the continuous furnace tunnel is the better option to the processing of industrialized food products. The fuel used in the burners is usually natural gas, which despite the uncertainties and fluctuantions in costs, is becoming more popular in national industry. In this work, several three-dimensional physical models were developed - classified in testing models, parametric analysis and optimization - and used to the study, modeling and optimization of continuous food furnaces of tunnel type with indirect heating. It was chosen the OpenFOAM® opensource software for modeling of proposed problems. The geometry and the operating conditions were based in a bauruense food company to the process of pre-baking of pizzas. The effects of geometry, mesh, initial and boundary conditions, pressure-velocity coupling algorithm, field strengths, radiation heat exchanges using fvDOM and view/Factor, and modeling RANS k - E for turbulence to were evaluated about the flow parameters. The SIMPLE is the most indicated pressure-velocity coupling algorithm to this problem. The use of viewFactor radiation model proved more adequate. The heat exchanges by convection over the treadmill have proved little significant compared the heat exchanges by radiation, demonstrating the importance of correct modeling of this phenomenon. Differents geometries tests were made, and the furnace with the smaller ratio aspect geometric and, consequently, smaller height, showed to be most efficient, although this may result in practice, in limitations in its use